Synthesis and Antimicrobial activity of 2-Chloroquinoline Incorporated Pyrazoline Derivatives. - Bibhu P Panda; Rajiv kumar; Suresh Kumar; Sushma Drabu; Sandhya Bawa (Wolters Kluwer Medknow Publications, 2009)
A series of 2-chloroquinoline containing pyrazoline derivatives were synthesized and screened for their antimicrobial activity against a panel of bacterial and fungal strains by cup plate method. The structures of newly synthesized compound were established on the basis of spectral data obtained from the FTIR, 1H & 13C-NMR and mass spectrometry. Among the compound tested 3,4-dichloro derivatives were comparatively more active in antimicrobial screening with respect to their 3,4-dimethoxy analogue.